<p>if f(x+1) = 3x2 + 6x + 3 then f(x) =

answer : 3x2

howww :s</p>

<p>if you factor out the equation, you get </p>

<p>3(x+1)(x+1)</p>

<p>if you substitute x for the (x+1)s, then you would get what f(x) is:</p>

<p>you get 3(x)(x) which is 3x^2</p>

<p>same as above…</p>

<p>Thaaanks :)</p>

<p>actually i didnt really get it u substitute it (x+1) only in 3x2 why not in the rest of the equation???

here is another qs of same type

if f and g are functions such that g(x)= 3x+2 and f(g(x))=9x+5 then f(x)= </p>

<p>thanks in advance :)</p>

<p>ohhhhh yes yes i got it hhhh thanks</p>

<p>if x is a real number, which of the following is a graph of the solution set of (x-3)(2-x) greater than or equal to zero?

the answer is 2<x<3 but="" i="" got="" x<2="" and="" x="">3 !!

can u please tell me what is my mistake :)</x<3></p>

<p>heyyyyyyyyyyyyyyy

:)</p>